Chinese gods : the unseen world of spirits and demons - Stevens, Keith, 1926- (London : Collins and Brown, 1997)
Een uitgebreide kennismaking met de Chinese godenwereld: tempels, altaren, communicatie met de goden, het taoisme, het confucianisme, het boeddhisme, gezondheid en medicijnen, huwelijk, kinderen, welzijn en succes in zaken, landbouw, natuur, zee en rivieren, de onderwereld en de doden.
ChronologyMap -- Pronouncing Chinese words -- Glossary -- Iconography -- Temples & altars -- Communication with & worship of deities -- Creation & prehistory -- Taoist deities -- Confucian deities -- Buddhist deities -- Stellar deities of fate & destiny -- Health & medicine -- Deities of marriage & child rearing -- Wealth & success in business -- Agriculture & nature deities -- Deities of the seas & rivers -- Deified worthies -- The local spirit bureaucracy -- The underworld & the dead -- Index of Deities' names.
Paralleltit. in chines. Schriftz
Keywords: China -- Religious life and customs; Gods, Chinese